Educational research : the interrelationship of questions, sampling, design, and analysis - Schreiber, James; Asner-Self, Kimberly (Wiley/Jossey-Bass education, 2011)
"Researchers finally have a resource that focuses on the research question, providing them with a unique approach that will help in the field. Key Ideas sections presented in each chapter act as an organising mechanism and look at the big picture of that chapter. Many of the writing activities are open-ended questions that allow them to write questions or what they are thinking about the topic at that point. In-Text Activities ask them to write down what they are working on, such as a research question, review of literature, or potential sample. Case study examples are also integrated throughout to demonstrate how decisions are made and how they affect everything in a study. This enables researchers to create the most effective studies"--Provided by publisher